Business Information Systems Workshops BIS 2013 International Workshops, PoznaD, Poland, June 19-20, 2013, Revised Papers - Abramowicz, Witold. (Lecture Notes in Business Information Processing, 2013)
This book constitutes the refereed proceedings of the four workshops that were organized in conjunction with the International Conference on Business Information Systems, BIS 2013, which took place in PoznaD, Poland, in June 2013. BIS workshops give researchers the opportunity to share their preliminary ideas and first experimental results and to discuss research hypotheses with a highly focused audience. The 25 papers in this volume were carefully reviewed and selected from 47 submissions and were revised and extended after the event. The workshop topics covered applications and economics of knowledge-based technologies (AKTB), business and IT alignment (BITA), enterprise systems for higher education (ESHE), and formal semantics for future enterprises (FSFE). In addition, two keynotes as well as ten papers presented at the PhD Symposium are also included in this volume.